2023
DOI: 10.1186/s12885-023-10927-x
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer screening utilization and its predictors among women in bench Sheko Zone, Southwest Ethiopia: using health belief model

Abstract: Background Cervical cancer is the fourth most frequently diagnosed and found to be the leading cause of cancer death in women, especially in low and middle-income countries. Even though cervical cancer is a preventable disease, its preventive measures have not been equitably implemented across and within different countries; especially in low and middle-income countries, due to different contributing factors. Objective This study aimed to assess ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…When the significantly associated demographic characteristic variables and correlated HBM domains with regularity of performing PTB prevention practices were further analyzed to determine the significantly independent predictors of adopting PTB prevention practices ( Table 7 ), we found that having an underlying disease, perceived benefits of PTB prevention or screening, and belief in Islam (inverse prediction) were the significant independent predictors. Several previous studies confirmed the significant influence of mostly perception of benefits and barriers of HBM domains and level of understanding or knowledge on the people's decision to participate in cancer screening or health education programs ( 7 10 , 32 ). Moreover, health educations focusing on encouraging the domains of the HBM, reducing all possible barriers to access to healthcare service, and understanding how to practice disease prevention could promote self-efficacy in practicing self-care finally ( 11 13 , 33 , 43 – 46 ).…”
Section: Discussionmentioning
confidence: 58%
“…When the significantly associated demographic characteristic variables and correlated HBM domains with regularity of performing PTB prevention practices were further analyzed to determine the significantly independent predictors of adopting PTB prevention practices ( Table 7 ), we found that having an underlying disease, perceived benefits of PTB prevention or screening, and belief in Islam (inverse prediction) were the significant independent predictors. Several previous studies confirmed the significant influence of mostly perception of benefits and barriers of HBM domains and level of understanding or knowledge on the people's decision to participate in cancer screening or health education programs ( 7 10 , 32 ). Moreover, health educations focusing on encouraging the domains of the HBM, reducing all possible barriers to access to healthcare service, and understanding how to practice disease prevention could promote self-efficacy in practicing self-care finally ( 11 13 , 33 , 43 – 46 ).…”
Section: Discussionmentioning
confidence: 58%
“…The GWAS dataset for the age of rst sexual intercourse in this study was obtained from the Medical Research Council-Integrative Epidemiology Unit (MRC-IEU) GWAS database 7 , UK Biobank, the Genome (PRACTICAL) Consortium, and the "MR-base" with unknown Consortium. The rst sexual intercourse age dataset (ID: ebi-a-GCST90000047) .…”
Section: Data Sourcementioning
confidence: 99%
“…the age of rst sexual intercourse(AFS) is related to premature birth and teenage pregnancy, as well as adverse health consequences such as depression, sexually transmitted diseases, and even certain cancers 3 , such as cervical cancer 4 . In addition to being associated with cervical cancer, the age of rst sexual intercourse is also associated with various cancers, such as lung cancer 5 , head and neck cancer 6 , cervical cancer 7 , prostate cancer 8 . Although many population-based studies have described the association between the age of rst sexual intercourse and multiple cancers, the mechanism of its action is still unclear, and the evidence of the association between the age of rst sexual intercourse and multiple cancers is still controversial.…”
Section: Introductionmentioning
confidence: 99%